2020
DOI: 10.2147/ccid.s194074
|View full text |Cite
|
Sign up to set email alerts
|

<p>Conventional and Novel Treatment Modalities in Rosacea</p>

Abstract: Rosacea is a common skin disease that is troublesome for both the patients and the dermatologists. Erythema, telengiectasia, papulopustular changes and phymatous changes are the main problems faced by the patients and dermatologists in everyday practice. Due to the chronic and relapsing nature of the disease, patients are usually unsatisfied with conventional treatment methods. This article aims at redefining rosacea according to the 2017 consensus and reviewing the different treatment modalities for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(79 reference statements)
0
8
0
5
Order By: Relevance
“…15 Hence, the development of therapeutics that address these challenges can significantly improve the treatment and care of rosacea. 16,17 Recently, an ionic liquid/deep eutectic solvent comprised of choline and geranic acid (CAGE) has been shown to exhibit characteristics that make it a potential candidate for effective treatment of rosacea. Specifically, prior in vitro studies have shown that CAGE exhibits excellent antimicrobial activity against a broad variety of pathogens 18,19 including Staphylococcus epidermidis which could be associated with pustules of rosacea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Hence, the development of therapeutics that address these challenges can significantly improve the treatment and care of rosacea. 16,17 Recently, an ionic liquid/deep eutectic solvent comprised of choline and geranic acid (CAGE) has been shown to exhibit characteristics that make it a potential candidate for effective treatment of rosacea. Specifically, prior in vitro studies have shown that CAGE exhibits excellent antimicrobial activity against a broad variety of pathogens 18,19 including Staphylococcus epidermidis which could be associated with pustules of rosacea.…”
Section: Introductionmentioning
confidence: 99%
“…They are also limited by treatment cost, poor dermal permeation, and have certain regional restrictions of manufacturing 15 . Hence, the development of therapeutics that address these challenges can significantly improve the treatment and care of rosacea 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…6 A variety of treatment modalities have been reviewed, including skin care and cosmetic treatments, topical therapies, oral therapies, laser-and light-based therapies, injection therapies, and combination therapies, based on their anti-demodex, anti-inflammatory, and anti-angiogenesis effects. [36][37][38][39] However, recalcitrant, refractory, and persistent rosacea remains challenging in rosacea treatment. 12,40 Botulinum toxin, especially type A, has many off-label uses in aesthetic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It has a significant negative effect on the quality of life and is a risk factor for depression and anxiety. [1,2] The main symptoms of rosacea are erythema, telangiectasia, edema, papules, pustules, stinging, and hot flushes. Recently, the international prevalence of rosacea was reported to be approximately 5.5%.…”
Section: Introductionmentioning
confidence: 99%